Effect of Ag Nanoparticles on Denitrification and Microbial Community in a Paddy Soil - Zhang, Xiao; Dang, Di; Zheng, Lingsi; Wu, Lingyu; Wu, Yu; Li, Haoruo; Yu, Yongjie (Frontiers in Microbiology, 2021)
The extensive application of Ag nanoparticles (AgNPs) in industry, agriculture, and food processing areas increases the possibility of its release and accumulation to agroecosystem, but the effects of AgNPs to denitrification and the microbial community in paddy ecosystems are still poorly studied. In this study, microcosmic simulation experiments were established to investigate the response of soil denitrification to different levels of AgNPs (i.e., 0.1, 1, 10, and 50 mg/kg) in a paddy soil. Real-time quantitative PCR and high-throughput sequencing were conducted to reveal the microbial mechanism of the nanometer effect. The results showed that, though 0.1–10 mg/kg AgNPs had no significant effects on denitrification rate and N2O emission rate compared to CK and bulk Ag treatments, 50 mg/kg AgNPs significantly stimulated more than 60% increase of denitrification rate and N2O emission rate on the 3rd day (P < 0.05). Real-time quantitative PCR revealed that 50 mg/kg AgNPs significantly decreased the abundance of 16S bacterial rRNA gene, nirS/nirK, cnorB, and nosZ genes, but it did not change the narG gene abundance. The correlation analysis further revealed that the cumulative N2O emission was positively correlated with the ratio of all the five tested denitrifying genes to bacterial 16S rRNA gene (P < 0.05), indicating that the tolerance of narG gene to AgNPs was the key factor of the increase in denitrification in the studied soil. High-throughput sequencing showed that only the 50-mg/kg-AgNP treatment significantly changed the microbial community composition compared to bulk Ag and CK treatments. The response of microbial phylotypes to AgNPs suggested that the most critical bacteria which drove the stimulation of 50 mg/kg AgNPs on N2O emission were Firmicutes and β-proteobacteria, such as Clotridiales, Burkholderiales, and Anaerolineales. This study revealed the effects of AgNPs to denitrification in a paddy ecosystem and could provide a scientific basis for understanding of the environmental and toxicological effects of Ag nanomaterials.